Comparative Genomics Between Saccharomyces kudriavzevii and S. cerevisiae Applied to Identify Mechanisms Involved in Adaptation - Macías, Laura G.; Morard, Miguel; Toft, Christina; Barrio, Eladio (Frontiers in Genetics, 2019)
Yeasts belonging to the Saccharomyces genus play an important role in human-driven fermentations. The species S. cerevisiae has been widely studied because it is the dominant yeast in most fermentations and it has been widely used as a model eukaryotic organism. Recently, other species of the Saccharomyces genus are gaining interest to solve the new challenges that the fermentation industry are facing. One of these species is S. kudriavzevii, which exhibits interesting physiological properties compared to S. cerevisiae, such as a better adaptation to grow at low temperatures, a higher glycerol synthesis and lower ethanol production. The aim of this study is to understand the molecular basis behind these phenotypic differences of biotechnological interest by using a species-based comparative genomics approach. In this work, we sequenced, assembled and annotated two new genomes of S. kudriavzevii. We used a combination of different statistical methods to identify functional divergence, signatures of positive selection and acceleration of substitution rates at specific amino acid sites of proteins in S. kudriavzevii when compared to S. cerevisiae, and vice versa. We provide a list of candidate genes in which positive selection could be acting during the evolution of both S. cerevisiae and S. kudriavzevii clades. Some of them could be related to certain important differences in metabolism previously reported by other authors such us DAL3 and ARO4, involved in nitrogen assimilation and amino acid biosynthesis. In addition, three of those genes (FBA1, ZIP1 and RQC2) showed accelerated evolutionary rates in Sk branch. Finally, genes of the riboflavin biosynthesis were also among those genes with a significant higher rate of nucleotide substitution and those proteins have amino acid positions contributing to functional divergence.